1984
DOI: 10.1038/312767a0
|View full text |Cite
|
Sign up to set email alerts
|

T-lymphocyte T4 molecule behaves as the receptor for human retrovirus LAV

Abstract: Many viruses, including retroviruses, are characterized by their specific cell tropism. Lymphadenopathy-associated virus (LAV) is a human lymphotropic retrovirus isolated from patients with acquired immune deficiency syndrome (AIDS) or related syndromes, that displays selective tropism for a subset of T lymphocytes defined by the expression of a surface glycoprotein of relative molecular mass 62,000 (62K) termed T4 (refs 6-8). This glycoprotein delineates a subset of T lymphocytes with mainly helper/inducer fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
1,011
2
16

Year Published

1987
1987
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 2,239 publications
(1,041 citation statements)
references
References 15 publications
12
1,011
2
16
Order By: Relevance
“…Previous reports have shown the lower incidence of developing AIDS for HIV + patients who received immunosuppressive therapy with cyclosporin A (CsA) after organ transplantation [1][2][3]. Moreover, in response to the immunosuppressive drugs CsA and FK506, the growth of cells chronically infected with HIV-1 and HIV-2 was selectively inhibited [4].…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports have shown the lower incidence of developing AIDS for HIV + patients who received immunosuppressive therapy with cyclosporin A (CsA) after organ transplantation [1][2][3]. Moreover, in response to the immunosuppressive drugs CsA and FK506, the growth of cells chronically infected with HIV-1 and HIV-2 was selectively inhibited [4].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the functional spikes, there is also evidence for the presence of nonfunctional derivatives, such as gp41 stumps and gp120/gp41 monomers, on the viral surface (54,66). Most variants of HIV-1 enter cells through attachment of the envelope spike to the main cellular receptor CD4 (15,39), which triggers a conformational change allowing interaction with a cellular coreceptor, typically CCR5 or CXCR4 (53), eventually leading to fusion of virus and cell membranes. Potent entry inhibitors can target various stages of this process (51).…”
mentioning
confidence: 99%
“…The identification of CD4 as the major virus receptor was very important, particularly as few virus receptors were known then [12]. Early studies revealed differences among HIV isolates to replicate in macrophages versus T-cell lines that correlated with their cytopathology (e.g.…”
Section: Sequence Diversitymentioning
confidence: 99%